Size- and time-dependent alteration in metabolic activities of human hepatic cytochrome P450 isozymes by gold nanoparticles via microsomal coincubations - Ye, Meiling; Tang, Ling; Luo, Mengjun; Zhou, Jing; Guo, Bin; Liu, Yangyuan; Chen, Bo (Nanoscale research letters, 2014)
Nano-sized particles are known to interfere with drug-metabolizing cytochrome P450 (CYP) enzymes, which can be anticipated to be a potential source of unintended adverse reactions, but the mechanisms underlying the inhibition are still not well understood. Herein we report a systematic investigation of the impacts of gold nanoparticles (AuNPs) on five major CYP isozymes under in vitro incubations of human liver microsomes (HLMs) with tannic acid (TA)-stabilized AuNPs in the size range of 5 to 100 nm. It is found that smaller AuNPs show more pronounced inhibitory effects on CYP2C9, CYP2C19, CYP2D6, and CYP3A4 in a dose-dependent manner, while 1A2 is the least susceptible to the AuNP inhibition. The size- and dose-dependent CYP-specific inhibition and the nonspecific drug-nanogold binding in the coincubation media can be significantly reduced by increasing the concentration ratio of microsomal proteins to AuNPs, probably via a noncompetitive mode. Remarkably, AuNPs are also found to exhibit a slow time-dependent inactivation of 2D6 and 3A4 in a β -nicotinamide adenine dinucleotide 2′-phosphate reduced tetrasodium salt hydrate (NADPH)-independent manner. During microsomal incubations, UV–vis spectroscopy, dynamic light scattering, and zeta-potential measurements were used to monitor the changes in particle properties under the miscellaneous AuNP/HLM/CYP dispersion system. An improved stability of AuNPs by mixing HLM with the gold nanocolloid reveals that the stabilization via AuNP-HLM interactions may occur on a faster time scale than the salt-induced nanoaggregation by incubation in phosphate buffer. The results suggest that the AuNP induced CYP inhibition can be partially attributed to its adhesion onto the enzymes to alter their structural conformations or onto the HLM membrane therefore impairing the integral membrane proteins. Additionally, AuNPs likely block the substrate pocket on the CYP surface, depending on both the particle characteristics and the structural diversity of the isozymes. These findings may represent additional mechanisms for the differential inhibitory effects arising from the coincubated AuNPs on the metabolic activities of the hepatic CYP isozymes.